Relation Between Anthropometric Muscle Mass Characteristics of Lower Limbs and Jump Power in Young Athletes - Benavides-Roca, Luis (2021)
Regional anthropometry turns out to be an important procedure in the projection of the athlete’s performance. The objective of the present study is to relate the anthropometric characteristics of the lower limbs of the body with the jumping power of young athletes. A correlational methodology was used to evaluate 44 youth athletes (30 men and 14 women). They were measured for jump height in 90° squat (SJ), countermovement with fixed hands (CMJ-MF), and countermovement with free hands (CMJ-ML). These variables derived into the power calculation. With this, we established the anthropometric characteristic of lower body parts linked to skinfolds and perimeters, obtaining values of mid (MMED) and maximum thigh (MMAX), corrected calf perimeter (PCP), quadriceps muscle section area (ASMC), hamstring muscular section area (ASMI), and total section of the muscular thigh area (ASMM). The results showed a significant correlation between the corrected calf perimeter and the jump power in SJ (r=0.73; p=0.00), CMJ-MF (r=0.72; p=0.00) and CMJ-ML(r=0.7; p=0.00). In conclusion, the calf perimeter presented related components to the young athletes’ jumping power.